Commentary: The Idea on Motion (Actual Motion) In 3-Dimensional Visual Art - Mazlan, Hilal (Idealogy Journal; Vol 4 No 2 (2019): Idealogy Journal (September 2019), 2019)
Letter to Editor - No Abstract